Effects of super absorbent polymer with different application rates on soil characteristics and flue-cured tobacco growth in Qinba mountain area - BAI Gangshuan; GENG Wei; HE Dengfeng (浙江大学学报. 农业与生命科学版)
In order to improve soil characteristics, reduce the effect of seasonal drought on the growth of fluecured tobacco, and promote the application of super absorbent polymer in flue-cured tobacco production, we analyzed the effects of different super absorbent polymer application rates on soil moisture, soil bulk density, fluecured tobacco growth, conventional chemical composition and economic characteristics. The potassium polyacrylate super absorbent polymer of 45, 60 and 75 kg/hm2 was separately applied to the tobacco field with yellow brown soil in Qinba mountain area, and no super absorbent polymer was applied as a control. The results showed that the application rate of 75 kg/hm2 had a relatively large effect on the soil moisture from seedling survival stage to rosette stage of flue-cured tobacco, while the treatment with application rate of 60 kg/hm2 had a relatively greater effect on soil moisture from flourishing growth stage to after maturity stage. However, different application rates of potassium polyacrylate super absorbent polymer had no significant effect on soil moisture from seedling survival stage to after maturity stage. The soil bulk density of 0-20 and >20-40 cm soil layers was significantly reduced by the treatment with application rate of 60 kg/hm2, but the treatments with application rate of 45 and 75 kg/hm2 had no significant effect on soil bulk density. All application rates of potassium polyacrylate super absorbent polymer promoted the growth of flue-cured tobacco, increased flue-cured tobacco yield, conventional chemical composition and output value. The proportion of superior tobacco significantly increased, while the proportion of inferior tobacco significantly decreased, and the net output value of the fluecured tobacco significantly increased by the treatment with application rate of 60 kg/hm2. In sum, the suitable application rate of potassium polyacrylate super absorbent ploymer is about 60 kg/hm2 in the tobacco field with yellow brown soil in Qinba mountain area.